“La retención de los vehículos ejecutada por los Agentes de Policía en las contravenciones de tránsito de primera clase y su incidencia en el principio a la seguridad jurídica en la Unidad Judicial Penal del Cantón Riobamba, durante el período agosto 2014 – agosto 2015.” - Castelo Granizo, Gabriela Verónica (2016)
The present research work lets us know if the vehicles retention by police officers in transit first-class infractions strikes in principle to legal certainty in the Criminal Justice Unit in Riobamba canton, period August 2014 - August 2015. Our Constitution is protective of rights therefore the legal system should not be contrary to it; the organic comprehensive criminal code which entered into force on 10 August 2014, this code was trying to unify all punitive regulations, so that the legislator in infringement of transit of first class article 386 of the mentioned legal body second paragraph establishes the sanction of retention as well as the fine and points reduction, police officers retain the vehicle unless the offender has exercised his right to a defense. The involved sample in the investigative process is 24 among judges, lawyers and police officers whom I have surveyed to verify the hypothesis. This research is characterized as a non-experimental field, type exploratory, descriptive and explanatory research; the results of the problem are based on the analysis, interpretation with which we express that the retention of the vehicle carried out by police officers affects the principle legal security by applying a sanction prior to a process and existence of a ruling firm. The first Chapter, Referential framework, which alludes to the problem, the objectives to achieved with research; The second Chapter, Theoretical framework develops units raised in the project, so doctrinaire and review, based on the variables of the problem, and is the operationalization of variables; The third Chapter, Methodological framework, the scientific method, the type of research, the research design, the involved population, techniques and instruments that we apply in the present research, the results analysis and discussion, and finally testing the hypotheses if we reject it, we accept or it is null; The fourth Chapter, Conclusions and recommendations resulting from the research field, and the doctrinal analysis.